Effect of Organic Extract Sprays on Growth and Biomass Production of Seedlings of Two Important Multipurpose Trees - Vijayananthan, K.; Kumar, M. Ganesh; Gopi, D. (Indian Journal of Agroforestry, 2020)
An attempt was made to study the effect of organic extracts on growth and biomass production of two important multipurpose trees. Among the organic extracts, spraying of vermiwash II exerted the maximum influence on all the growth parameters in teak seedlings while vermicast extract produced the maximium growth parameters on casuarinas. It was followed by vermiwash I. Spraying of cow dung extract did not produce any significant effect in either of these seedlings.